2005
DOI: 10.1007/s10967-005-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Long range transport of biomass aerosol to Greenland: Multi-spectroscopic investigation of particles deposited in the snow

Abstract: Results are given from the NIST component of a pilot ("winter-over") study of seasonal patterns of natural and anthropogenic species in air and snow transported to Summit, Greenland. Central to this research is the quantitative apportionment of fossil and biomass particulate carbon, based on advanced (micromolar) 14 C accelerator mass spectrometry (AMS) applied to remote snow samples containing as little as 9 µg C/kg. The measurements were made practicable through stringent attention to the nature and sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The main sources of carboxylic acids for Central Greenland lie in North America and Asia, from where air trajectories reach the ice cap after a very short track over the North Atlantic, especially over the Arctic Ocean (Kahl et al, 1997). This offers the possibility to better approach the part of the carboxylic cycle related to natural continental sources (biomass burning from the boreal forest, and biomass and soil emission from lower latitudes (Currie et al, 2005). On the contrary, Antarctica is surrounded by a very vast expanse of ocean, so the continental influence remains very restricted under the present climate conditions.…”
Section: Background á Atmospherementioning
confidence: 99%
“…The main sources of carboxylic acids for Central Greenland lie in North America and Asia, from where air trajectories reach the ice cap after a very short track over the North Atlantic, especially over the Arctic Ocean (Kahl et al, 1997). This offers the possibility to better approach the part of the carboxylic cycle related to natural continental sources (biomass burning from the boreal forest, and biomass and soil emission from lower latitudes (Currie et al, 2005). On the contrary, Antarctica is surrounded by a very vast expanse of ocean, so the continental influence remains very restricted under the present climate conditions.…”
Section: Background á Atmospherementioning
confidence: 99%
“…Specific organic compounds, including PAHs [ Jaffrezo et al , 1993] and particulate oxalate [ Jaffrezo et al , 1998; Kerminen et al , 1998], have been measured at Summit, Greenland (the highest point of the Greenland Ice Sheet). In addition, major biomass burning episodes impacting the air above the Greenland Ice Sheet were detected through atmospheric measurements of oxalate [ Jaffrezo et al , 1998], 14 C [ Currie et al , 2005], and black carbon [ Stohl et al , 2006]. To our knowledge, there are no other reported measurements of particulate carbonaceous species in the Greenland atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…107 It has been revealed that up to 25% of insoluble aerosols are bioaerosols, 108 which can travel long distances and end up on snow. 109–111 Fig. 3 and 5a–d show some examples of particles, including biological particles of different sizes, from a few nanometers to a few micrometers, in Arctic snow samples.…”
Section: Snow Particle Physicochemical Characterization: Anthropogeni...mentioning
confidence: 99%